When International Dynamics and Domestic Interests Collide: Australia’s Decision in a Quest for Nuclear-Powered Submarines - Agnes Deandra Bangkur; Yandry Kurniawan (Journal for Peace and Nuclear Disarmament, 2025)
The process of making foreign policy decisions has always been a contested area where international dynamics and domestic interests collide. Sometimes, a country must take a hard turn at the crossroads and make a decision different from the general trend or even its established national identity. This is the case with Australia’s decision to enter AUKUS and acquire nuclear-powered submarines, a move that has received negative responses due to the country’s long-time established identity as a non-nuclear state. In this article, we explore the relationship between international dynamics and domestic interests to explain the possible factors the Australian government considered when acquiring nuclear-powered submarines under the AUKUS alignment. We argue that the combination of factors such as the international system, international law including treaty commitments, history of alignment and traditions, military capabilities and industrial military complex, as well as party interests, may lead to unpopular decisions that are contrary to a country’s foreign policy general trend and long-time established identity.